О переваривании крахмала и белка корневым луковым клещом (Rhizoglyphus echinopus Fum. et Rob., 1868) - Барабанова, В.В. (Вестник зоологии, 1972)
Optimal conditions of total proteolytic activity and amylase activity were studied in Rhizoglyphus echinopus F u m. et R o b. Laboratory culture of Rh. echinopus served as a material. Protease and amylase activity was determined at different values of pH and temperatures. The highest proteolytic activity was observed in a neutral zone at pH 7.0. Optimal temperature for proteases is 35° C. For amylases the optimal value of pH is 6.0. With incubation temperature rise the enzyme activity increases. Temperature 50° C was not critical for amylase.